Nurses’ functional status assessments using the International Classification of Functioning, Disability, and Health across hospital types in Japan: A cross-sectional study - Yamamoto, Kanako (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: In Japan, patients receiving treatment in advanced acute care hospitals often cannot return home immediately and require ongoing hospitalization. Sequential support is crucial to facilitate long-term recovery and community reintegration. Therefore, functional assessments should extend beyond physical function to include daily activities and participation. However, how nurses across different hospital types in Japan evaluate patients’ functional status using a standardized framework remains unclear. Objective: This study examined how nurses in hospitals with varying care functions assess patients’ functional status, focusing on the application of the International Classification of Functioning, Disability, and Health (ICF) framework. Methods: A cross-sectional survey with a qualitative component was conducted in accordance with the STROBE guidelines. Participants were 200 registered nurses in Japan, each with at least three years of clinical experience. Data were collected from February to March 2025 through an online survey using a commercial research firm’s verified panel of licensed nurses. Quantitative data were analyzed using descriptive statistics, chi-square tests, and one-way analysis of variance (ANOVA). In addition, open-ended responses were analyzed qualitatively to capture contextual perspectives on functional assessment. Results: No significant differences were observed in discharge planning practices among the four hospital types. The Functional Independence Measure was most frequently used in recovery-phase hospitals (p <0.001). Across all hospital types, assessments focused primarily on body functions and structures, while activities and participation domains received comparatively less attention. Qualitative analysis indicated that the focus of patient handovers varied by hospital function, reflecting institutional roles and priorities. Conclusion: Although discharge planning practices were comparable across hospital types, functional assessments remained concentrated on physical aspects, with limited attention to broader domains critical for long-term recovery. These findings highlight the need for a more comprehensive and standardized use of the ICF framework to support patients’ social reintegration and continuity of care across healthcare settings.